PEMBERDAYAAN EKONOMI MASYARAKAT PEDESAAN DI MASA PANDEMI MELALUI PELATIHAN TANAMAN HIDROPONIK DALAM KETERBATASAN LAHAN DI DESA KERTAANGSANA - Aeni Latifah; Indah Parwansyah; Oktavian Ihda Sumantri (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
Social interaction to prevent the spread of the virus in the midst of society, this causes the economy of Indonesian society to decline. Community empowerment programs, especially in economic aspects, are needed today, so as students who are carrying out Real Work Lecture activities are required to be able to provide new knowledge to the community to increase insights and help find new business innovations in the agricultural sector that can increase rural income. The program carried out is hydroponic plant training for farmers and PKK mothers in Kertaangsana Village, Nyalindung Subdistrict, Sukabumi Regency. The method of conducting this training is to provide face-to-face counseling, introduce hydroponic plant technology, and carry out direct practice. Participants' understanding success rates were measured from the results of questionnaires distributed to participants. Questions about hydroponics have been able to be answered by participants with a percentage of 85%. All participants argued that hydroponic plant training is very useful, among others, can increase community motivation in utilizing limited yards or land and used goods, can also help the community make new breakthroughs to improve the economic welfare of the community, especially rural communities